How Things Feel: Biblical Studies, Affect Theory, and the (Im)Personal - Kotrosits, Maia ca. 20./21. Jh. (Brill research perspectives in Biblical interpretation, 2016)
This essay is an intellectual history, one of affect theory both within and without biblical studies, rendered as an ecology of thought. It is an “archive of feelings,” a series of thematic portraits, and a description of the landscape of the field of biblical studies through a set of frictions and express discontentments with its legacies, as well as a set of meaningful encounters under its auspices. That landscape is recounted with a fully experiential map, intentionally relativizing those more dominant sources and traditional modes of doing intellectual history. Affect theory and biblical studies, it turns out, both might be described as implicitly, and ambivalently, theological. But biblical studies has not only typically refused explicit theologizing, it has also refused explicit affectivity, and so affect theory presents biblical studies with both its own losses and new and vital possibilities.